Kerjasama Pengelolaan Perbatasan Indonesia–Malaysia: Prospek dalam Mewujudkan Kawasan Perbatasan yang Aman dan Sejahtera - Ridwan Maulana; Christoforus Arel S. Heuk; Yusa Djuyandi (Public Knowledge, 2026)
Border areas are a strategic manifestation of territorial sovereignty for national integrity and natural resource management. However, these regions often face complex challenges regarding human security, such as poverty and food insecurity. This research aims to explore the dynamics of bilateral cooperation between Indonesia and Malaysia in realizing a secure and prosperous border, focusing on the land territory of Kalimantan as well as the maritime regions of the Malacca Strait and the Celebes Sea. Using a qualitative descriptive-analytical approach with a case study method, this research relies on secondary data from policy documents and academic literature. The research results identify five main dimensions of cooperation: territorial boundary affirmation, security (joint patrols), economy (revitalization of State Border Posts), social-labor relations, and environmental protection. Although institutional cooperation has been established, its effectiveness is hindered by maritime delimitation disputes, economic development disparities, the prevalence of illegal activities through "unofficial paths" (jalur tikus), and weak domestic inter-agency coordination. Theoretically, this study emphasizes that regional stability is no longer sufficient through traditional security approaches alone; community welfare and access to basic services have become the primary keys. As a future strategy, this research recommends accelerating diplomacy for boundary disputes, digitalizing surveillance through drone technology, and empowering the local economy through MSMEs to strengthen national loyalty. Academically, this research contributes to international relations studies regarding functional border governance that balances sovereignty control with the dynamics of cross-border socio-economic interaction.   Wilayah perbatasan merupakan manifestasi kedaulatan teritorial yang strategis bagi keutuhan negara dan pengelolaan sumber daya alam. Namun, kawasan ini sering menghadapi tantangan kompleks terkait keamanan manusia (human security), seperti kemiskinan dan kerawanan pangan. Penelitian ini bertujuan mengeksplorasi dinamika kerjasama bilateral Indonesia–Malaysia dalam mewujudkan perbatasan yang aman dan sejahtera, dengan fokus pada wilayah darat Kalimantan serta kawasan maritim Selat Malaka dan Laut Sulawesi. Menggunakan metode kualitatif deskriptif-analitis dengan studi kasus, penelitian ini mengandalkan data sekunder dari dokumen kebijakan dan literatur akademik. Hasil penelitian mengidentifikasi lima dimensi utama kerjasama: penegasan batas wilayah, keamanan (patroli bersama), ekonomi (revitalisasi Pos Lintas Batas Negara), sosial-ketenagakerjaan, dan perlindungan lingkungan. Meskipun kerjasama institusional telah terjalin, efektivitasnya terhambat oleh sengketa delimitasi maritim, ketimpangan pembangunan ekonomi, maraknya aktivitas ilegal melalui "jalur tikus", serta lemahnya koordinasi antarlembaga domestik. Secara teoritis, kajian ini menekankan bahwa stabilitas kawasan tidak lagi cukup hanya dengan pendekatan keamanan tradisional; kesejahteraan masyarakat dan akses terhadap layanan dasar menjadi kunci utama. Sebagai strategi ke depan, penelitian ini merekomendasikan percepatan diplomasi sengketa batas, digitalisasi pengawasan melalui teknologi drone, serta pemberdayaan ekonomi lokal melalui UMKM untuk memperkuat loyalitas nasional. Secara akademik, penelitian ini berkontribusi pada kajian hubungan internasional mengenai tata kelola perbatasan fungsional yang menyeimbangkan kontrol kedaulatan dengan dinamika interaksi sosial-ekonomi lintas batas.